Changes in Cervical Human Papillomavirus (HPV) Prevalence at a Youth Clinic in Stockholm, Sweden, a Decade After the Introduction of the HPV Vaccine - Ährlund-Richter, Andreas; Cheng, Liqin; Hu, Yue O. O.; Svensson, Mikaela; Pennhag, Alexandra A. L.; Ursu, Ramona G.; Haeggblom, Linnea; Grün, Nathalie; Ramqvist, Torbjörn; Engstrand, Lars; Dalianis, Tina; Du, Juan (Frontiers in cellular and infection microbiology, 2019)
This study aimed to follow the impact of human papillomavirus (HPV) catch-up and vaccination on the very high cervical HPV-prevalence in women at a youth clinic in central Stockholm during the period 2008-2018. 2008-2010, cervical HPV-prevalence (69.5%) and HPV16 prevalence (34.7%) were high in non-vaccinated women at a youth clinic in Stockholm. 2013-2015, after the introduction of the quadrivalent-Gardasil® HPV-vaccine, HPV16 and HPV6 prevalence had decreased. Here, cervical HPV-prevalence was investigated 10 years after primary sampling. 2017-2018, 178 cervical swabs, from women aged 15-23 years old, were tested for 27 HPV types by a bead-based multiplex method. HPV-prevalence data were then related to vaccination status and age and compared to HPV-prevalence in 615 samples from 2008 to 2010 and 338 samples from 2013 to 2015 from the same clinic, and to HPV types in 143 cervical cancer cases during 2003-2008 in Stockholm. The proportion of vaccinated women increased from 10.7% (2008-2010) to 82.1% (2017-2018). The prevalence of all 27 HPVs, all high-risk HPVs (HR-HPVs) and the combined presence of the quadrivalent-Gardasil® types HPV16, 18, 6, and 11, was lower in vaccinated compared to unvaccinated women (67.4 vs. 93.3%, = 0.0031, 60.1 vs. 86.7%, = 0.0057 and 5.8 vs. 26.7%, = 0.002, respectively). Furthermore, HPV16 prevalence in non-vaccinated women 2017-2018 was lower than that in 2008-2010 (16.7 and 34.7%, respectively, = 0.0471) and similar trends were observed for HPV18 and 11. In both vaccinated and non-vaccinated women, the most common non-quadrivalent-Gardasil® vaccine HR-HPV types were HPV39, 51, 52, 56, and 59. Together they accounted for around 9.8% of cervical cancer cases in Stockholm during 2003-2008, and their prevalence tended to have increased during 2017-2018 compared to 2008-2010. Quadrivalent-Gardasil® vaccination has decreased HPV-vaccine type prevalence significantly. However, non-vaccine HR-HPV types remain high in potentially high-risk women at a youth clinic in Stockholm.